The Role of Islamic Education on Students' Multiculturalism Awareness - Trysha Yulindaputri; Ahmad Arifi; Khoirul Anam (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Multicultural awareness is very important for students to have, because diversity often triggers disharmony in relationships between students. Based on this, Islamic education is very important in the socio-cultural dialectical transformation which is expected to develop social culture, in relation to the diversity of society. The aim of this research is to analyze the role of Islamic education on students' multicultural awareness. This research uses qualitative research by conducting a literature review which involves searching for information in books and articles on topics related to the research topic. The results of the research show that the role of Islamic education is to form Indonesian people who have faith and devotion to God Almighty and have noble character and are able to maintain peace and harmony, relations between religious communities. To increase the diversity of students with their respective religious beliefs and provide the possibility of openness to foster an attitude of tolerance towards other religions. In this context, religious teaching taught in schools is required to always instill the values of religious tolerance. The next role is to educate children, the younger generation and adults to become true Muslims and believers.